Regulated Improvisations: bringing the private sector back into the International Development Cooperation field - Esteves,Paulo (2020)
Abstract This article questions why and how the private sector was articulated as a legitimate agent in a field almost entirely dominated, until the 2000s, by DAC donors. We argue that private agents were admitted in the field across the fractures produced by SSCP and throughout a series of normative and managerial adjustments, which we called here regulated improvisations.